AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-2351
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Design Optimization and Shape Exploration using Generative Adversarial Networks

Abstract: Global optimization of aerodynamic shapes requires a large number of expensive CFD simulations because of the high dimensionality of the design space. One means to combat that problem is to reduce the dimension of the design space-for example, by constructing low dimensional parametric functions (such as PARSEC and others)-and then optimizing over those parameters instead. Such approaches require first a parametric function that compactly describes useful variation in airfoil shape-a non-trivial and error-pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Finally, in both methods, we use the soft vicinal loss (it was observed that the soft vicinal loss performed better in both methods across all examples) and pick and based on the rule of thumb method described by [11]. In the Airfoil example we used a residual neural network (ResNet) [16] trained on the dataset as the estimator model and a BézierGAN [8] to generate airfoils. In this example we refer to the continuously conditioned Bézier-GAN as 'CcGAN' and the BézierGAN with L as 'PcDGAN'.…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in both methods, we use the soft vicinal loss (it was observed that the soft vicinal loss performed better in both methods across all examples) and pick and based on the rule of thumb method described by [11]. In the Airfoil example we used a residual neural network (ResNet) [16] trained on the dataset as the estimator model and a BézierGAN [8] to generate airfoils. In this example we refer to the continuously conditioned Bézier-GAN as 'CcGAN' and the BézierGAN with L as 'PcDGAN'.…”
Section: Model Configurationmentioning
confidence: 99%
“…This assumption is impractical in many engineering design settings since performance is usually continuous. For example, in turbine design, some important performance metrics are the power coefficient, the pressure coefficient, and the cavitation number [23]; in aerodynamic design, performance is measured by lift to drag ratio or inverse lift coefficient [8]; in beam design, common metrics are compliance and natural-frequency [2] -these metrics are all continuous variables. To use those metrics as the condition in conditional generative models, past work [1,25] proposes to discretize the continuous values of the metrics to discrete bins.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest a great potential for the nonlinear MD-CNN-AE to be used for feature extraction of flow fields in lower dimension. Chen et al [136] applied CNN-based GANs to reduce the dimension of input airfoil shapes to realize the design optimization of an airfoil. CNNs are better than traditional approaches (e.g.…”
Section: B Feature Extractionmentioning
confidence: 99%
“…Deep learning [39] refers to neural networks with a large number of hidden layers. Deep learning has gained significant popularity in recent years as advances in computing power, such as massively parallel GPU architectures, and custom software, such as TENSOR-FLOW [40], have enabled the training of deep neural networks to process large datasets with impressive results in the machine learning [38,41] and design communities [37,42]. However, training deep learning networks requires access to very large amounts of training data to fit thousands of associated network parameters.…”
Section: Neuralmentioning
confidence: 99%